Clinical evaluation of arthrodesis with Ilizarov external fixator for the treatment of end-stage ankle osteoarthritis: A retrospective study. Issue 52 (24th December 2020) - Ma, Nan; Li, Zhi; Li, Delei; Hu, Yehua; Sun, Ning
Abstract : Abstract: To analyze the efficacy of arthrodesis with Ilizarov external fixator for the treatment of end-stage ankle osteoarthritis. This retrospective study included 88 patients with end-stage (stage-3) ankle osteoarthritis according to Morrey–Wiedeman classification who underwent arthrodesis with Ilizarov external fixator from January 2016 to January 2019. There were 47 males and 41 females with a mean age of (57.21 ± 7.12) years old (range 49–76). Outcomes were measured by the American Orthopaedic Foot and Ankle society (AOFAS) Ankle Hindfoot Scale, Visual Analog Scale (VAS) pain scores, complications, subjective satisfaction, ankle function, correction of deformity, and complications. With an average follow-up of (13.50 ± 5.41) months (range 10–21), all 88 patients returned for final follow-up. All patients achieved bony healing with a success rate of 100%. Mean postoperative healing time (3.56 ± 1.04) months (range 3–6). Two patients developed sinus tract infection, delayed healing in 1 patient, and 2 patients had pain and swelling again in the ankle joint. No serious complications occurred in other patients. All the patients evaluated with the VAS scores and AOFAS scores at final follow-up showed significant improvement ( P  < .05). Through imaging analysis, medical tibial talar angle (MTTA) improved from (85.76 ± 6.01) degrees to (88.98 ± 1.35) degrees postoperative. Lateral talar station (LTS) decreased from (5.32 ± 3.81) mm to (2.71 ± 2.62) mm after operation ( P  < .05). The overall satisfaction of patients is 88.64%. In the treatment of end-stage ankle osteoarthritis, arthrodesis with Ilizarov external fixator can achieve good radiological and clinical outcomes with low prevalence of ankle joint malalignment and high fusion rates and satisfaction.